The gut microbial composition in polycystic ovary syndrome with hyperandrogenemia and its association with steroid hormones - Li, Miao; Chang, Qiurong; Luo, Ye; Pan, Jiaping; Hu, Ye; Liu, Binya; Ma, Mengmeng; Wang, Qiaoling; Guo, Yi; Wang, Qian (Frontiers in Cell and Developmental Biology, 2024)
Background: Polycystic ovary syndrome (PCOS) is characterized by excess androgens, ovulatory dysfunction, and polycystic ovaries. The mechanisms underlying ovulatory and metabolic disorders in PCOS remain elusive, hampering therapeutic development. Enhanced metabolic health correlates with increased microbiota gene content and microbial diversity. We aimed to explore the impact of gut microbiota and serum steroids on PCOS regulation associated with androgen excess.The fecal samples of patients with hyperandrogenic PCOS (n = 14) and control group with PCOS (n = 14) were analyzed by 16S rRNA gene sequencing. The peripheral venous blood of all subjects was collected to detect serum hormones. The association between gut microbiota and serum hormones was analyzed with the R language.Results: Our findings reveal that the hyperandrogenic PCOS group exhibits lower richness and diversity of gut microbiota compared to the control group. Characteristic genera in PCOS patients with hyperandrogenism include Bifidobacterium, Enterobacteriaceae_unclassified, Streptococcus, Saccharimonadaceae, Enterococcus, and Eubacterium_nodatum_group. Five hormones, including 5β-androsterone, deoxycorticosterone, corticosterone, 11-dehydrocorticosterone, and cortexolone, emerge as potential serum biomarkers for identifying patients with hyperandrogenic-PCOS (HA-PCOS). Furthermore, a lower vitamin D3 level may act as a susceptibility factor, suggesting that vitamin D3 supplementation could serve as a potential intervention for PCOS with hyperandrogenism.Conclusions: Specific fecal microbiota and serum steroids may be used as characteristic markers for clinical diagnosis of hyperandrogenic-PCOS. This research enhances our understanding of the intricate interplay among hormones, gut microbiota, and hyperandrogenemia in patients with PCOS.